PENERAPAN PRINSIP TRANSPARANSI DAN MANAJEMEN PELAYANAN INFORMASI PUBLIK KOTA MEDAN DI DINAS KOMINFO - Patricia Herpayanti Rajagukgkuk; Gabriel Hutagaol; Jonson Rajagukguk; Maringan Panjaitan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Good governance can be understood by imposing characteristics, namely participation, law enforcement, transparency, equality of responsiveness, future insight, accountability, supervision, efficiency and effectiveness. But what you want to discuss is information transparency. Information transparency is openness in carrying out decision making and openness in expressing material and relevant information about the company. While transparency is the principle that guarantees access or freedom for everyone to obtain information about the administration of government and other activities, namely information about policies, the process of making, and the implementation and results achieved. This study uses a descriptive qualitative research method using interview and observation techniques. The study used